IT for E-Commerce, Financial Literacy, Financial Inclusion and Smes Performance: Mediating Role of Spiritual Value - Yuni Maulida; Bedjo Santoso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of this study is that to examine the effect of IT for e-commerce, financial literacy and financial inclusion on the performance of SMEs with spiritual value as a moderating variable. In general, the company faces challenges in maintaining superior business performance over a long period. Furthermore, most companies find it difficult to continuously achieve business performance which suitable to the strategic insight and agility to ensure the business environment. Resource based View and Technology Acceptance Model was the theory which underlay this study. This study used a sample of 180 SMEs in Central Java. In addition, the data analysis method in this study used multiple regression analysis with the SmartPLS version 3 application. The result shows that IT for e-commerce and financial literacy has a significant positive effect on financial inclusion. Meanwhile, IT for e-commerce has no significant positive effect on SMEs performance. Financial literacy and financial inclusion have a significant positive effect on SMEs performance. In addition, spiritual values are able to moderate the relationship between IT for e-commerce, financial literacy and financial inclusion on SMEs performance.